Assessing the compressive strength of concrete under sustained actions: From refined models to simple design expressions. (12th March 2019) - Tasevski, Darko; Fernández Ruiz, Miguel; Muttoni, Aurelio
Abstract : The detrimental influence of high levels of sustained load on the compressive strength of concrete has been acknowledged and investigated since the 1950s. Despite the potential significance of this phenomenon in many situations, current design codes still provide limited guidance on how to account for this effect at ultimate limit state. In addition, the practical case of a significant permanent stress followed by stress increases due to variable loads is not addressed in most codes of practice. The aim of this paper is to present a general but simple design approach to account for the influence of sustained loading on the uniaxial behavior of concrete in compression, both in terms of its strength and deformation capacity. This approach is based on a previously developed mechanical model accounting for nonlinear creep and material damage development on the long‐term response of concrete. On that basis, a design approach is formulated in a simple code‐like manner and used to investigate several practical design situations involving both sustained and variable actions. This approach is shown to be consistent and applicable to any general loading pattern, accurately reproducing the results of the general mechanical model and of available experimental results.